Производство ствольного железа на казенных горных заводах Урала в середине XIX в. - Шумкин, Г.Н. (Історичний архів. Наукові студії, 2014)
Рассмотрено производство ствольного железа на казенных горных заводах Урала в
1830-х – 1850-х гг. Показано, как низкое качество ствольного железа повлияло на
степень готовности русской армии к Крымской войне и на развитие
железоделательного производства на Урале. Розглянуто виробництво ствольного заліза на казенних гірничих заводах Уралу в
1830-х – 1850-х рр. Висвітлено, як низька якість ствольного заліза вплинула на рівень
готовності російської армії до Кримської війни і на розвиток металургійного
виробництва на Уралі. In the first half of the XIX century in the military industry of Russia there is a system of
relations in which the state-owned mountains factories were obligated to produce the metal for
the army and the Navy, and military plants were obligated to accept this metal for weapons of
subjects. Due to the monopoly position of state-owned mountains factories supplied the iron for
the musket barrel low quality. In the 1830s the problem with the quality of the barrel iron
aggravated, because in Europe have started modernization of armies the fast charge rifles
which shot in 3-4 times further that muskets. At the end of the 1830s and 1840s was mastered
several production technologies iron. In the 1850s, was built Nykolayivsk small-arms factory.
However, the quality of the barrel’s iron remained low. As a result, by the beginning of the
Crimean war of 1853-1856 years in the British army every second soldier was equipped the
rifled musket, in the French army – every third, and in the Russian army – only one out of 20. In
late 1850-s production the barrel’s iron was mastered at the Izhevsk plant. From 1862 the
demand for the barrel iron was reduced, because the Tula and Sestroretsky plants the part of
the barrels started manufacturing of the steel of German manufacturer Berger. On the agenda
was the problem of organization of production the barrels of the steel. This problem was solved
in the 1880s when the Izhevsk factory started production of barrel steel. Solution to problem of
the barrel iron by abolishing the mandatory relations between the state-owned mountains
factories and the small-arms factories has become the precedent, after which Military and
Marine Ministry demanded the complete elimination the monopoly of the state-owned
mountains factories for the supply of metal, ammunition and artillery of the army and Navy. In
1868, the government went to meet them. Since that time, the state-owned mountain plants
were deprived of almost all privileges that were used in the military industry.